El Edificio Caldas: un Edificio de Alta Tecnología al Servicio de la Educación - Cardenas C, Roberto (Ingeniería, 2000)
This article presents the technical considerations that will make possible The Caldas Building (in construction now) be in accordance with nowadays Universidad Distrital´s demands related to laboratories, classrooms and facilities devoted to engineering teaching, which are included into The Advanced Controlled Campus project as part of its global University virtual environment project.